Physiological and physical effect on U-12 and U-15 football players, with the manipulation of task constraints: field size and goalkeeper in small-sided games of 4x4 players. [Efecto fisiológico y físico en los jugadores de fútbol Sub-12 y Sub-15, con la manipulación de las restricciones de tareas: tamaño de campo y portero en juegos reducidos de jugadores 4x4]. - Fernando Jorge Santos; Teresa Figueiredo; Cátia Ferreira; Mário Espada (Ramón Cantó Alcaraz, 2021)
Our study aimed to verify whether the manipulation of task constraints has different effects according to age group. Another objective was to verify the physiological and physical responses in the different formats of small-sided games (SSG). Each team in the SSGs was composed of 4 players (4x4). The participants in the research are young football players U-12 (n=8) and U-15 (n=8), affiliated with a club certified as a training entity, and competed in the regional football championship of 7 and 9 players and the national championship of Portugal, respectively. The internal and external load data were collected in 5 formats of SSGs with three field size and in 2 used goalkeepers. We used the WIMU PROTM inertial device for data collection. The registration of the internal charge, using heart rate (HR), was performed with the use by the players of Garmin bands, which send the data to WIMU PROTM devices, through of Ant+ technology. The variance analysis (ANOVA) was used to verify the differences between SSGs and the effect size was determined by calculating partial eta-square). Comparisons between the two age groups were evaluated using standardized differences with combined variance (Cohen's d). The results show that the manipulation of the playing areas and the use of goalkeepers promoted different effects in the two age groups in terms of distance, explosive distance, accelerations/decelerations and maximum sprint. As for the comparison between SSGs we found differences in the level of external load (distance, accelerations/decelerations and maximum sprint). At the level of internal load, the effects were more evident with field areas above 100m2. We can conclude that the manipulation of the task conditions, playing area and goalkeeper, promote different physical and physiological responses, and the coach should consider this fact, as well as the effects promoted in the age groups.